2015
DOI: 10.3390/w7062796
|View full text |Cite
|
Sign up to set email alerts
|

Climate or Land Use?—Attribution of Changes in River Flooding in the Sahel Zone

Abstract: This study intends to contribute to the ongoing discussion on whether land use and land cover changes (LULC) or climate trends have the major influence on the observed increase of flood magnitudes in the Sahel. A simulation-based approach is used for attributing the observed trends to the postulated drivers. For this purpose, the ecohydrological model SWIM (Soil and Water Integrated Model) with a new, dynamic LULC module was set up for the Sahelian part of the Niger River until Niamey, including the main tribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 60 publications
6
53
0
1
Order By: Relevance
“…Finally, in research on the relative impact of human and natural factors, Aich et al [93], observed both a general return to wet conditions since the end of the 1980s and an increase in annual maximum discharge in the NRB (Niger River Basin) for the same time period.…”
Section: The Onset Of the Monsoon Through Agronomical Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, in research on the relative impact of human and natural factors, Aich et al [93], observed both a general return to wet conditions since the end of the 1980s and an increase in annual maximum discharge in the NRB (Niger River Basin) for the same time period.…”
Section: The Onset Of the Monsoon Through Agronomical Criteriamentioning
confidence: 99%
“…In cultivated areas of the Sahel, the extension of soil "erosion-crusting" (see description below) [72,76] has led to directly exposing topsoil to successive intense rainfall events and severe drying episodes. This "erosion-crusting" mainly concerns newly cropped typical Sahelian sandy soils and is most often assumed to be a consequence of land clearing and extension of cropping [6,93,94] (land use change). In pastoral areas, during the drought, the removal of the thin lithosol by wind or water erosion, occurring because of the vegetation dying, led rocks to outcrop [16,49,72,95] (land cover change).…”
Section: Highlighting the Correlation Between Land Use/land Cover Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have used hydrological modelling (based on different scale, basin, data set and model) to infer the role of climate and LULC on hydrological changes in West Africa since 1950(1950-1998: Seguis et al, 2004, 1951: D'Orgeval and Polcher, 2008, 1950-2009: Aich et al, 2015. The conclusions differ among these studies: D'Orgeval and Polcher (2008) found that LULC was less important than rainfall changes, in contrast to Seguis et al (2004), while Aich et al (2015) concluded on the role of both LULC and climate. presented a preliminary work between 1983 and 2012, and showed that rainfall variability alone could explain the observed changes in the Niger River hydrograph in Niamey over the last 30 years.…”
Section: Introductionmentioning
confidence: 99%
“…The first strategy is to couple dynamic drivers (e.g., climate, LULC, soils, topography and human infrastructure) to hydrological models [22]. For example, a dynamic LULC module can quantify the contribution of land use change to river flooding [24]. The other approach is to adapt physical or conceptual hydrological models to changing conditions by estimating parameter travel in real time or near real time [19].…”
Section: Introductionmentioning
confidence: 99%